2014
DOI: 10.1111/jen.12135
|View full text |Cite
|
Sign up to set email alerts
|

Development of a standardized protein immunomarking protocol for insect mark–capture dispersal research

Abstract: A field study was conducted to test the marking efficiency of broadcast spray applications of protein marks on stationary (represented by cadavers) and free‐roaming lady beetles Hippodamia convergens Guérin‐Méneville that were strategically placed in blooming alfalfa plots. The marks tested included three different concentrations of egg albumin from chicken egg white, casein from bovine milk and trypsin inhibitor from soy milk. The cadaver and free‐roaming beetle treatments served to measure the acquisition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 31 publications
2
24
1
2
Order By: Relevance
“…These results support previous studies that showed that egg white is a more steadfast mark than bovine and soy milk (Jones et al, 2006;Hagler & Jones, 2010;Slosky et al, 2012;Hagler et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results support previous studies that showed that egg white is a more steadfast mark than bovine and soy milk (Jones et al, 2006;Hagler & Jones, 2010;Slosky et al, 2012;Hagler et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…However, 22.1 and 5.1% of the bovine milk‐ and soy milk‐marked H. convergens , respectively, did not retain their mark. These results support previous studies that showed that egg white is a more steadfast mark than bovine and soy milk (Jones et al., ; Hagler & Jones, ; Slosky et al., ; Hagler et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, they showed that different water sources, additives (surfactants), and even the type of ELISA plate used affected (either positively or negatively) the assay. Moreover, that study and subsequent studies 37,39,40 showed that the three protein mark detection assays vary in efficacy. The egg white marker was retained longer than the milk marker, which was retained longer than soy milk marker.…”
Section: Introductionmentioning
confidence: 99%
“…Future users of the immunomarking technique should ensure that their methodology is suitable to the specifics of their research. The concentration and volume of the mark needed and how the mark is applied will depend on factors like behavior, body type and size of the target species 40 .…”
Section: Introductionmentioning
confidence: 99%